Competition policy and patent law under uncertainty : regulating innovation - Manne, Geoffrey A.; Wright, Joshua D. (Cambridge : Cambridge University Press, 2011)
The regulation of innovation and the optimal design of legal institutions in an environment of uncertainty are two of the most important policy challenges of the twenty-first century. Innovation is critical to economic growth. Regulatory design decisions and, in particular, competition policy and intellectual property regimes can have profound consequences for economic growth. However, remarkably little is known about the relationship between innovation, competition and regulatory policy. Any legal regime must attempt to assess the trade-offs associated with rules that will affect incentives to innovate, allocative efficiency, competition, and freedom of economic actors to commercialize the fruits of their innovative labors. The essays in this book approach this critical set of problems from an economic perspective, relying on the tools of microeconomics, quantitative analysis and comparative institutional analysis to explore and begin to provide answers to the myriad challenges facing policymakers.
pt. 1. The institutions of growth: Legalize freedom : a chapter on law and policy for innovation and growth / Robert D. Cooter ; What is so special about intangible property? : the case for intelligent carryovers / Richard A. Epstein -- pt. 2. The economics of innovation: Bundling and unbundling in new technology markets : seven easy pieces : the ideal is the enemy of the efficient / Stan J. Liebowitz and Stephen E. Margolis ; Unlocking technology : antitrust and innovation / Daniel F. Spulber ; Creative construction : assimilation, specialization, and the technology life cycle / Marco Iansiti and Gregory L. Richards -- pt. 3. Innovation and competition policy: Favoring dynamic over static competition : implications for antitrust analysis and policy / David J. Teece ; Antitrust, multidimensional competition, and innovation : do we have an antitrust-relevant theory of competition now? / Joshua D. Wright ; American and European monopolization law : a doctrinal and empirical comparison / Keith N. Hylton and Haizhen Lin -- pt. 4. The patent system: Rewarding innovation efficiently : the case for exclusive rights / Vincenzo Denicolò and Luigi Alberto Franzoni ; Presume nothing : rethinking patent law's presumption of validity / Douglas G. Lichtman and Mark A. Lemley ; Patent notice and cumulative innovation / Michael Meurer -- pt. 5. Property rights and the theory of patent law: Commercializing property rights in inventions : lessons for modern patent theory from classic patent doctrine / Adam Mossoff ; The modularity of patent law / Henry E. Smith ; Removing property from intellectual property and (intended?) pernicious impacts on innovation and competition / F. Scott Kieff -- pt. 6. Intellectual property and the antitrust : the regulation of standard-setting organizations: Increments and incentives : the dynamic innovation implications of licensing patents under an incremental value rule / Anne Layne-Farrar, Gerard Llobet, and Jorge Padilla ; What's wrong with royalties in high-technology industries? / Damien Geradin ; Federalism, substantive preemption, and limits on antitrust : an application to patent holdup / Bruce H. Kobayashi and Joshua D. Wright.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Patent laws and legislation; Competition, Unfair; Technological innovations -- Law and legislation; Antitrust law